Observation of self-assisted GaAs nanowire growth by molecular beam epitaxy on GaAs (1 1 1)B without SiO2 layer. (15th September 2017) - Vorathamrong, Samatcha; Panyakeow, Somsak; Ratanathammaphan, Somchai; Praserthdam, Piyasan; Tongyam, Chiraporn
Abstract: GaAs nanowire growth was performed on bare GaAs (1 1 1)B substrates by molecular beam epitaxy technique. A small adjustment was made to the conventional self-assisted VLS growth by removing covered SiO2 layer and growing nanowires directly on the substrate surface in order to eliminate some issues that occur in the conventional self-assisted VLS growth. To study the growth mechanism, growth time was varied as a growth parameter. Nanowire crystal structure was investigated by XRD analysis. Evolution of surface morphology along with RHEED patterns were utilized to determine characteristics of the growth.